Preconditioning and Uniform Convergence for Convection-Diffusion Problems Discretized on Shishkin-Type Meshes. (28th February 2016) - Nhan, Thái Anh; Vulanović, Relja
Abstract : A one-dimensional linear convection-diffusion problem with a perturbation parameterɛ multiplying the highest derivative is considered. The problem is solved numerically by using the standard upwind scheme on special layer-adapted meshes. It is proved that the numerical solution isɛ -uniform accurate in the maximum norm. This is done by a new proof technique in which the discrete system is preconditioned in order to enable the use of the principle where "ɛ -uniform stability plusɛ -uniform consistency impliesɛ -uniform convergence." Without preconditioning, this principle cannot be applied to convection-diffusion problems because the consistency error is not uniform inɛ . At the same time, the condition number of the discrete system becomes independent ofɛ due to the same preconditioner; otherwise, the condition number of the discrete system before preconditioning increases whenɛ tends to 0. We obtained such results in an earlier paper, but only for the standard Shishkin mesh. In a nontrivial generalization, we show here that the same proof techniques can be applied to the whole class of Shishkin-type meshes.